Diagnosis Penyakit Cabai Dengan Menggunakan Metode Forward Chaining - Dempster-Shafer - Eka Hery Wijaya; Nurul Hidayat; Suprapto Suprapto (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Chili pepper (Capsium annum l.) is a commodity many vegetables that get attention because it has a fairly high economic value needs increasing the longer the chili annually in line with the development of an industry that requires Chili, raw material of this plant to be one of the types of plants that are desperately needed by everyone in Indonesia because the majority of the population of Indonesia likes spicy food. In the last few years there have been many farmers began to plant the cabaisebagai one of the alternatives in the farm. Almost every citizen of Indonesia need a chili pepper used to add spicy flavors in the dish. Cabaibesar is a one of a kind hybrid chili pepper which is very sought after by farmers to cultivated because it has a high economic value. Drew poduktif and have a broad market. This system design method using Forward Chaining and Dempster-Shafer to provide suggestions or considerations to farmers to determine superior varieties of chili peppers. The result of this method of the form perangkingan. Method of Forward Chaining inference engine functions as based on the facts that exist after it was calculated with the method of Dempster-Shafer. In this study performed a test by measuring the level of accuracy that produce value the accuracy of 90%. So that the system that is created by using the method of Forward Chaining and Dempster-Shafer can be applied to diagnose diseases in crops of chili.